La innovación en la micro y la pequeña empresa (MYPE): no solo factible, sino accesible - Ponce Regalado, Fátima (2017)
The present paper seeks to point out that innovation is also accessible and necessary for the micro and small entreprises (MSE) in Latin America. But it is not given as traditionally understood as associated to technology. The hypothesis is that innovate in the MSE is not impossible nor necessarily expensive; on the contrary it is necessary and feasible, but different because it is related less to techonology than to processes or management models. In fact, several of these small businesses are making that in order to promote their growth and sustainability. To evidence this hypothesis and show that the regional innovation is rather in processes and/or management models, aspects where small firms have great opportunities to innovate and improve their productivity, this work analyzes statistics both in Costa Rica and Peru. The purpose is to define the MSEs main features, the owners skills and their innovation environment, in order to make visible its competences and the kind of innovation focus more in processes and management models and less in products or technology. It also presents two successful cases in generation of innovations with the purpose of presenting how the MSE are able to apply new measures and redirect their course when necessary.